Staff perceptions following a training programme about reducing psychotropic medication use in adults with intellectual disability: The need for a realistic professional practice framework. Issue 3 (19th January 2023) - Barratt, Macey; Jorgensen, Mikaela; Deb, Shoumitro (Shoumi); Limbu, Bharati; Donley, Mandy; Buchholtz, Moira; Smith, Victoria; Wilson, Nathan
Abstract: Background: Adults with intellectual disability are at higher risk of being administered psychotropic medications. The UK‐developed SPECTROM (Short‐term PsychoEducation for Carers To Reduce Over Medication of people with intellectual disabilities) training programme educates disability support workers on psychotropic medications and alternatives to these medications. Method: Interviews were conducted with 10 participants who took part in the pilot SPECTROM training programme to elicit their views on the programme and its appropriateness in an Australian context. Results: The key theme was 'Need for a psychotropic medication practice framework'. Four sub‐themes were Broad satisfaction with the SPECTROM training programme; Disability support workers acknowledging the limitations of their scope of practice; Empowering training through prescriptive and reflective methods and; Need for future mentoring from Multi‐Disciplinary Team members in the application of new knowledge. Conclusions: Participants felt that whilst they could improve their knowledge and attitudes surrounding psychotropic medication administration for behaviours of concern through SPECTROM training, a national practice framework is needed to execute its goals at scale.